Impact of Rehabilitation on Breast Cancer Related Fatigue: A Pilot Study - Invernizzi, Marco; de Sire, Alessandro; Lippi, Lorenzo; Venetis, Konstantinos; Sajjadi, Elham; Gimigliano, Francesca; Gennari, Alessandra; Criscitiello, Carmen; Cisari, Carlo; Fusco, Nicola (Frontiers in Oncology, 2020)
Breast cancer fatigue (BCF) is a complex and multidimensional condition characterized by a persistent sense of physical and/or mental stiffness, resulting in a substantial impairment of health-related quality of life in breast cancer patients and survivors. Aim of this prospective cohort study was to evaluate the feasibility and the effectiveness of a 4-week rehabilitation protocol on BCF, muscle mass, strength, physical performance, and quality of life in breast cancer (BC) survivors. We recruited adult BC women with a diagnosis of BCF, according to the International Classification of Diseases 10 criteria, referred to the Outpatient Service for Oncological Rehabilitation of a University Hospital. All participants performed a specific physical exercise rehabilitative protocol consisting of 60-minute sessions repeated 2 times/week for 4 weeks. All outcomes were evaluated at the baseline (T0), at the end of the 4-week rehabilitation treatment (T1), and at 2-month follow up (T2). The primary outcome measure was the Brief Fatigue Inventory (BFI); secondary outcomes were: Fat-Free Mass and Fat Mass, assessed by Bioelectrical Impedance Analysis (BIA); Hand Grip Strength Test (HGS); Short Physical Performance Battery (SPPB); 10-meter walking test (10MWT); 6-minute walking test (6MWT); European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ–C30). Thirty-six women (mean age: 55.17±7.76 years) were enrolled in the study. We found a statistically significant reduction of BCF after the 4-week rehabilitation treatment (T1) (BFI: 5.4±1.6 vs 4.2±1.7; p=0.004) and at the follow-up visit (T2) (BFI: 5.4 ± 1.6 vs 4.4 ± 1.6; p=0.004). Moreover, we found significant differences (p<0.001) at T1 in terms of HGS, SPPB, 10MWT, 6MWT, and EORTC QLQ-C30. At T2, all the outcome measures significantly differ (p<0.05) from the baseline. The rehabilitation protocol seemed to be feasible, safe, and effective in reducing BCF, improving muscle mass and function, and improving HRQoL in this cohort of BC survivors. These results could improve awareness of this underestimated disease, suggesting the definition of a specific therapeutic exercise protocol to reduce BCF.